METHOD FOR SEPARATING RHENIUM FROM SOLUTION CONTAINING PERRHENIC ACID - TAKEDA KAZUNORI; KUBOTA NAOKI; KUDO TAKASHI; ASANO SATOSHI (2011)
PROBLEM TO BE SOLVED: To provide an inexpensive method, even if the content of rhenium in raw material is remarkably varied, which can stably and efficiently separate rhenium. SOLUTION: In the method for separating rhenium from a solution containing one or more elements selected from copper, zinc, cadmium and arsenic, and perrhenic acid, the method comprises: a first stage 1 where alkali such as sodium hydroxide is added to the solution so as to produce precipitates, and the solution containing the precipitates is subjected to solid-liquid separation by a separation process such as filtration; a second stage 2 where acid such as sulfuric acid is added to a separated liquid obtained by the solid-liquid separation, and the concentration of the acid is regulated to a range satisfying the equivalent concentration of 1.0 to 4.0 normal; and a third stage 3 where a sulfurizing agent such as sodium hydrogensulfide is added to the regulation liquid obtained by the addition of the acid so as to produce sulfide precipitates, and the sulfide precipitations are separated from the liquid after the sulfurization. COPYRIGHT: (C)2011,JPO&INPIT